Entrapped on the Web? Applying the Entrapment Defense to Cases Involving Online Sting Operations - Moore, Robert (American journal of criminal justice, 2007)
Many law enforcement agencies are currently responding to the problem of online crime by establishing proactive investigative units that track criminals on the Internet. Not only do these specialized teams face problems in the area of emerging technology, they are also faced with handling emerging legal issues. The current research examined the issue of the entrapment defense, and how previously established physical realm doctrine could be applied to the investigation of online crimes such as child pornography. Relying on previous case law it would appear that entrapment claims related to online sting operations involve consideration of: a) did the law enforcement officer continuously contact the suspect with the intention of trying to convince the individual to engage in a particular type of behavior, b) how long was the relationship between the undercover officer and the suspect, and c) how much, if any, reluctance to commit the criminal act did the suspect provide evidence of?